Strategi Pengembangan Sanggar Belajar Progresif Guna Peningkatan Kualitas Manajemen dan Akademik di Desa Ambulu Kabupaten Probolinggo - Darwin Djeni (Fakultas Ekonomi dan Bisnis Islam, 2018)
The purpose of this research is to know the strategic position of Progressive Learning Studio in Ambulu Village Probolinggo Regency and to determine strategy to improve management and akdemik to survive and develop from quantity and quality aspect. This research was conducted purposively in Sumberasih sub-district of Probolinggo. Analysis conducted by research method Diagram of SWOT analysis, External Factor Analysis Summary (EFAS) and Internal Factor Analysis Summary (IFAS). The results of the study are based on the results of the analysis on the SWOT diagram, from the total value of each factor can be explained that the most appropriate strategy is to compete in the guidance institution in the Sumberasih sub-district by way of improving the facilities and marketing progressive learning studio. The facilities in question are in terms of place and service optimal guidance process and a comfortable place. This is intended to be a different value from existing learning guidance, which is generally the institution stood in urban areas with a relatively high cost. Finally, the progressive learning studio has the opportunity and the power to develop in rural areas. Keywords: SWOT Analysis, Progressive Learning Studio, Quality Management, Academic.